Small Pancreas Neuroendocrine Tumors: How Small is Small? - Ming-Huang Chen; Chia Hsun Hsieh; Ching-Yao Yang; Hui-Jen Tsai; Li-Tzong Chen; On Behalf of Taiwan Neuroendocrine Tumor Society (Journal of Cancer Research and Practice)
Objective: The current study aimed to investigate the issues in contemporary management strategies that focus on small pancreatic neuroendocrine tumors (PNETs). Data Sources and Study Selection: We searched various scientific databases using specific keywords. Results: Surveillance-only strategies were considered for selected patients. The exact cut-off value of small neuroendocrine tumors for surveillance-only strategies needs to be verified with additional high-level evidence. Conclusion: There is no consensus on the size and treatment strategy for small PNETs currently. Patients with small nonfunctioning PNETs require individualized recommendations for surgery versus active surveillance based on tumor size, radiographic characteristics, and patient characteristics, such as age and comorbidities and also patient references.